MANAJEMEN PELAYANAN PRIMA: MENINGKATKAN KEPUASAN JEMAAH HAJI DAN UMRAH (STUDI KASUS MULTAZAM UTAMA TOUR) - Fikri Ilham; Zulhelmi (Jurnal Ekonomi dan Bisnis, 2024)
The background is to observe the growth of Hajj and Umrah pilgrims, encouraging research into the services provided and perceptions of pilgrims' expectations. Human resources are still lacking, namely not having permanent employees and the emergence of a mismatch between the services provided and the expectations of the congregation. The aim of the research is to explore how excellent service management can increase congregational satisfaction. This type of research is qualitative research carried out at the Multazam Utama Tour branch office in Bukittinggi City through observation, interviews and documentation. The results show the implementation of excellent service management through excellent service indicators in the form of; Reliability (Reliability), Responsiveness (responsiveness), Assurance (guarantee), Empathy (empathy), Tangibles (physical evidence). Efficient management, a complaint reporting system, a measurable reputation, a personal approach, as well as physical maintenance and the latest technology are the main factors in maintaining the quality of the Multazam Utama Tour Bukittinggi City service effectively in creating a perception of the congregation's expectations. Reliability is reflected in fulfilling service promises, responsiveness is reflected in response and alertness during the journey, assurance is formed through employee competence, empathy is reflected in attention to the special needs of the congregation, and physical evidence supports the good physical appearance of the building.